Healing Time and Complications in Operatively Treated Atypical Femur Fractures Associated With Bisphosphonate Use: A Multicenter Retrospective Cohort. Issue 4 (April 2016) - Bogdan, Yelena; Tornetta, Paul; Einhorn, Thomas A.; Guy, Pierre; Leveille, Lise; Robinson, Juan; Bosse, Michael J.; Haines, Nikkole; Horwitz, Daniel; Jones, Clifford; Schemitsch, Emil; Sagi, Claude; et al.
Abstract : Objectives: The purpose of this study was to characterize demographics, healing time, and complications of a large series of operatively treated atypical femur fractures. Design: Retrospective multicenter review. Setting: Seventeen academic medical centers. Patients: Bisphosphonate-related fractures as defined by American Society of Bone and Mineral Research. Fractures had to be followed for at least 6 months or to union or revision. Intervention: Operative treatment of bisphosphonate-related fracture. Main Outcome Measurements: Union time and complications of treatment, as well as information about the contralateral limb. Results: There were 179 patients, average age 72, average body mass index 27.2. Average follow-up was 17 months. Twenty-one percent had a previous history of fragility fracture; 34% had prodromal pain. Most (88%) lived independently before injury. Thirty-one percent had radiographic changes suggesting stress reaction. Surgical fixation was with cephalomedullary nail (51%), IM nail (48%), or plate (1%). Complications included death (4), PE (3), and wound infection (6). Twenty (12%) patients underwent revision at an average of 11 months. Excluding revisions, average union time was 5.2 months. For revisions, union occurred at an average of 10.2 months after intervention. No association was identified between discontinuation of bisphosphonates and union time ( P = 0.5) or need for revision ( P = 0.7). Twenty-one percent sustained contralateral femur fractures; 32% of these had pain and 59% had stress reaction before contralateral fracture. Conclusions: In this series, surgery had a 12% failure rate and delayed average time to union. Twenty-one percent developed contralateral femur fractures within 2 years, underscoring the need to evaluate the contralateral extremity. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.